2008
DOI: 10.4103/0970-4388.41624
|View full text |Cite
|
Sign up to set email alerts
|

Dentinogenesis imperfecta: A case report

Abstract: Dentinogenesis imperfecta is an autosomal dominant disorder of tooth development characterized by the presence of opalescent dentin, resulting in a dusky blue to brownish discoloration of the teeth. This condition is genetically and clinically heterogeneous; it may affect only the teeth or it may be associated with the osteogenesis imperfecta. Dentinogenesis imperfecta has been subdivided into three types: type I is associated with osteogenesis imperfecta; in type II there is no associated osteogenesis imperfe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…The term 'hereditary opalescent dentin' was first used by Skillen, Finn and Hodge. They used this particular term to explain the brown translucent teeth with opalescent sheen which lacked pulp chambers 4 . DI is known as hereditary opalescent dentin or Capdepont dysplasia 2 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The term 'hereditary opalescent dentin' was first used by Skillen, Finn and Hodge. They used this particular term to explain the brown translucent teeth with opalescent sheen which lacked pulp chambers 4 . DI is known as hereditary opalescent dentin or Capdepont dysplasia 2 .…”
Section: Discussionmentioning
confidence: 99%
“…Radiographically, the characteristic appearance is the bulbous crowns with constricted short roots 1,6 . Initially the pulp chambers are usually abnormally spacious and resemble "shell teeth," but then they will progressively obliterate giving the teeth solid appearance 4 . The teeth lack pulp chambers and root canals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The term was coined by Robert and Schor in 1939 4. Witkop reported that it was most common autosomal dominant disease affecting westerners 67…”
Section: Introductionmentioning
confidence: 99%
“…Radiographically type I and II exhibit identical changes 4-6. Opacification of dental pulp occur due continued deposition of abnormal dentin.…”
Section: Introductionmentioning
confidence: 99%